The roles of surface processes in porphyry copper deposit preservation - B. Hadler Boggiani; T. Salles; C. Mallard; N. Atwood (Earth Surface Dynamics)
Porphyry copper deposits typically originate within subduction zones at 2–5 km depths. These deposits are exhumed due to the influence of tectonic forces and climate-driven erosion. Porphyry copper deposits are currently only mineable at relatively shallow depths, and their prospectivity relies on a balance between the rate of exhumation and preservation. In this study, we evaluate the impact of surface processes on the preservation or exhumation of porphyry copper deposits. To do so, we rely on a global-scale numerical model (goSPL), which simulates landscape dynamics and associated erosion and deposition patterns over geological timescales. High-resolution Cenozoic simulations incorporate published open-source global paleo-climate and paleo-elevation datasets and have been fine-tuned using contemporary data. We then calculate exhumation rates by comparing the ages of known porphyry copper deposits and their simulated emplacement depths based on modeled erosion–deposition values. Obtained average exhumation rates vary from 10−2 to 10−1 km Myr−1, with an overall difference of 0.04 mm yr−1 when compared to independent erosion rate estimates available from published studies. The predicted global mean emplacement depths range from 1 to 3 km. To highlight the influence of paleo-reconstructions on exhumation rate estimates, we analyze simulated erosion rates across the Andean region using two distinct paleo-climate models and find significant spatial and temporal differences across the Central Andes. While our landscape evolution model successfully predicts the known emplacement depths for the North and South Andean deposits younger than 20 Myr, it also predicts depths exceeding 6 km for Central Andean deposits older than 60 Myr. We attribute these mismatches to a combination of limitations related to model assumptions and inputs resolutions. Our results show the intricate connection between deposit preservation and surface processes. Our method offers an addition to the traditional porphyry copper exploration toolkit that links geological observations to plate tectonics dynamics and paleo-climatic reconstructions.